The Sauropods : evolution and paleobiology - Curry Rogers, Kristina, 1974-; Wilson, Jeffrey A. (University of California Press, 2005)
This is a comprehensive scientific summary of the evolution and paleobilogy of Sauropod dinosaurs, the largest animals ever to walk the earth. Chapters address topics such as herbivory tracks, gigantism, locomotion, reproduction, growth rates and evolutionary history and diversity.